Hydrolytic Dephosphorylation of an Aryl Phosphoramidate - Archana Singh, Mrs.; Prabha, Shashi (Asian Journal of Chemistry, 2010)
Mono-2-NO2-4-CI phenyl phosphoramidate has been kinetically pursued for its hydrolysis at 50 ± 5°C and Allen's modified method has been employed for quantitative results. First order rate coefficients have been calculated in the entire acid range, 0.01-7.0 M HCI ionic strength studies lead to the fixed contribution of the undissociated form between 0.5-3.0 M, while the monoprotonated form solely contributed in the higher acid media, 4.0-7.0 M HCI. Beyond 4.0 M, water activity governs the rate of hydrolysis and a maximum number of three water molecules, derived from both Yates and McCleland correlation as well as Bronsted-Bjerrum equation, have been arrived at to transform the ester into its transition state. Solvent effect, concentration and Arrhenius parameters have been used to confirm the above results.